Nutritional status indices on the prognosis of patients with relapsed and refractory multiple myeloma treated with CAR-T cell immunotherapy - Xu, Peng; Liu, Yang; Wang, Yawen; Feng, Qiwen; Zhang, Huanxin; Cheng, Hai; Qi, Kunming; Xu, Kailin; Li, Zhenyu (Frontiers in Nutrition, 2025)
Background aimsChimeric antigen receptor (CAR) T-cell therapy shows remarkable efficacy against relapsed/refractory multiple myeloma (R/R MM). Nutritional status, assessed by objective indices like the Controlling Nutritional Status (CONUT) and Prognostic Nutritional Index (PNI), influences MM prognosis. However, their predictive value for outcomes following CAR-T therapy in R/R MM remains unclear.MethodsWe conducted a retrospective analysis of 181 R/R MM patients receiving CAR-T therapy. Patients were stratified by optimal CONUT (cutoff: 6.5) and PNI (cutoff: 42.75) scores determined via ROC analysis. Associations between CONUT/PNI and treatment outcomes were investigated.ResultsPatients with low CONUT or high PNI exhibited significantly improved progression-free survival (PFS) and overall survival (OS) compared to their counterparts (high CONUT or low PNI). While objective response rates (ORR) were high overall (approximately 90–95%), they did not differ significantly between CONUT or PNI subgroups. Importantly, low CONUT or high PNI was associated with faster hematopoietic recovery (red blood cells, hemoglobin, platelets, neutrophils, CD4+, CD8 + T-cells), lower incidence of prolonged hematologic toxicity (PHT), and higher peak CAR transgene levels. No significant differences were observed in cytokine release syndrome (CRS) or immune effector cell-associated neurotoxicity syndrome (ICANS) severity between subgroups. Multivariate analysis confirmed high CONUT as an independent risk factor for inferior PFS and OS, while low PNI was an independent risk factor for inferior PFS.ConclusionThis study establishes pretreatment CONUT and PNI as significant prognostic predictors for R/R MM patients undergoing CAR-T therapy. Patients with low CONUT or high PNI experience superior long-term survival outcomes, potentially linked to enhanced hematopoietic recovery and CAR-T cell expansion. These findings underscore the importance of nutritional assessment in prognostication and may guide future strategies to optimize CAR-T outcomes in R/R MM.